2008
DOI: 10.1001/archsurg.143.7.679
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplant for Hepatitis C Virus

Abstract: Hypothesis: Older donor grafts will provide suitable results of liver transplant, even in recipients with hepatitis C virus (HCV). Although HCV remains the leading indication for liver transplant in adults in the United States, it is associated with HCV recurrence, increased graft loss, and reduced survival. In addition, recent studies suggest that the use of older donors in recipients with HCV is associated with significantly worsened short-and longterm survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Many studies show lower patient and graft survival when using liver donors older than 60 years [9, 16–19, 53, 63, 64]. On the contrary, other authors did not find any significant differences in recipients of donors older than 60 and 70 years old compared with recipients of younger donors [12, 14, 22, 41, 43, 65]. When using donors older than 70 years, it has been shown that 1‐year patient survival varies between 69 and 95.4 %, 3‐year patient survival between 57.5 and 90.6 %, and 5‐year patient survival between 46.2 and 59.3 % [12, 14, 22, 40, 41, 43, 44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies show lower patient and graft survival when using liver donors older than 60 years [9, 16–19, 53, 63, 64]. On the contrary, other authors did not find any significant differences in recipients of donors older than 60 and 70 years old compared with recipients of younger donors [12, 14, 22, 41, 43, 65]. When using donors older than 70 years, it has been shown that 1‐year patient survival varies between 69 and 95.4 %, 3‐year patient survival between 57.5 and 90.6 %, and 5‐year patient survival between 46.2 and 59.3 % [12, 14, 22, 40, 41, 43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many authors have demonstrated significantly worse patient and graft survivals when liver grafts from donors older than 40–50 years are transplanted in HCV recipients [48–54]. However, as described in one recent report [65], we did not find significant differences in terms of 1‐, 3‐, and 5‐year patient survival ( P = 0.074) and graft ( P = 0.29) survival, between HCV recipients of liver grafts younger than 60 years and HCV recipients of liver grafts older than 60 years. In contrast, because of the tendency for patient survival to decrease at 5 years, with a longer follow‐up it should be possible to demonstrate a significantly poorer patient survival in HCV recipients of liver grafts from donors older than 60 years.…”
Section: Discussionmentioning
confidence: 99%